Engineering Fault-Tolerant Integration Architectures for Large-Scale Enterprise Workforce Systems - Mohammad, Abdul Jabbar (International Journal of AI, BigData, Computational and Management Studies, 2026)
Payroll, time tracking, calendar creation, worker management, and compliance reporting are all tasks that modern businesses require integrated workforce solutions for. To function properly, these systems must communicate in complex ways with HR platforms, ERP systems, identity services, and other organizations. These interfaces must remain consistent so that the business can continue to operate and employees can rely on them as organizations expand globally and adopt cloud-based workforce management solutions. It is nevertheless critical to ensure that large links between workers run properly and do not break down. Many companies continue to employ point-to-point integration technology to connect systems and transfer data. These principles are initially simple to implement, however they do not endure long. If one system fails, the data layout changes, or the network breaks, the other systems connected to it may also have issues. This could lead to issues with operations, late payments, and inconsistent data. When anything goes wrong, it usually takes a long time, costs a lot of money, and requires manual labor to correct. This paper discusses a fault-tolerant integration design for corporate workforce systems as a solution to these concerns. To prevent errors and failures, the design uses event-driven integration, asynchronous communication, and flexible coupling. The system includes centralized monitoring, message-driven orchestration, retry and compensation mechanisms, and idempotent processing. These make it simple to see what's happening and get back on track. Instead of viewing integrations as permanent data conduits, the new way of thinking regards them as processes capable of changing and repairing themselves. The major findings suggest that systems perform significantly better when they are designed to handle errors. This makes it easier to fix problems and add new features when integration gets more difficult. From a business perspective, the method reduces operational risk, ensures that people can keep their employment, and allows businesses to modernize their systems without putting them too close together. This article provides important tips for technology executives and integration builders on how to develop long-term ecosystems that will allow workers to collaborate in the future.